'Teaching without teaching' : critically exploring the involvement of visual artists in children's art classes in art museums of New Zealand : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Fine Arts, College of Creative Arts, Massey University, Wellington, New Zealand - Xu, Chang (Massey University, 2022)
Scholars in New Zealand have investigated museum education particularly in terms of young children’s visiting and learning, primary and intermediate students’ learning development, museum educators’ practice and challenges, and the policies, practices, and public pedagogy of visual art in art museum and gallery contexts. These scholars have indicated the importance of artists’ engagement in children’s art classes in art museums broadly speaking, but the specific investigation around this specific aspect was scant. This research aims to attend to this gap by exploring the engagement of visual artists in children’s art classes in art museums. The research acknowledges my position and background as a trained artist and teacher, and the roles I take on throughout the project also reflect this training and practice-based background. This study (including data collection and analysis, the conceptual development and iterative design process, and the forms of literature drawn upon) brings hybrid methodologies and references that span disciplines, including Participatory Action Research, Grounded Theory, Double Diamond design process, and a Co-design Approach. 24 interviews were conducted with visual artists and two workshops were developed with three different roles, including 6 artists, 3 museum educators, and 6 primary school teachers in two different art museums. The findings indicate a broadly effective collaboration between artists, museum educators, and primary school teachers with respect to complementing professional development, shifting to student-centred learning, expanding the forms of art activities based on students’ interests, developing a multisensory learning experience, and drawing theory from their practices. This research contributes to the field of museum education by developing a new form of collaboration between three different roles — artists, museum educators, and primary school teachers — in art museums, and conducting a collaborative reflection between these roles. This collaboration prototype becomes a way to effectively engage artists within children’s art museum education, and its benefits and impact can be documented and specified in various respects.
Keywords: Art; Study and teaching (Elementary); Art museums; Educational aspects; Artists as teachers; New Zealand; 360699 Visual arts not elsewhere classified; 430202 Critical heritage, museum and archive studies